Literature Review Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Balita - Sevti Maharani; Minarti Minarti (Yayasan Literasi Sains Indonesia, 2026)
In Indonesia, stunting cases showed a decline in 2024, namely 19.8% from the previous 21.5% in 2023. This remains a critical issue because it does not meet the WHO target. Stunting is a form of long-term malnutrition that can disrupt physical balance, cognitive development, and motor skills. This article was compiled by conducting a literature review of various sources found through search engines, such as Google Scholar or PubMed from the past five years, which includes research conducted specifically on the toddler population in Indonesia. The review results indicate various influencing factors, such as birth characteristics. Through analysis of various sources, it was concluded that there are many risk factors for stunting in Indonesia, such as maternal, child, and environmental factors. Maternal factors include the mother's age during pregnancy, maternal mid-upper arm circumference during pregnancy, maternal height, provision of breast milk or complementary foods, early initiation of breastfeeding, and food quality during pregnancy. Child factors include a history of low birth weight (LBW) or premature birth, male gender, a history of neonatal illness, persistent diarrhea, a history of infectious diseases, and the child's lack of immunizations. Environmental factors such as low economic status, limited family education, particularly for the mother, low family income, open defecation or inadequate toilets, unsafe drinking water, and high exposure to pesticides also contribute to increased stunting. Providing good nutrition for infants and toddlers can help improve stunting. Mothers also need to consume nutritious foods, especially during pregnancy.